Effect of Sawdust Addition on Thermal Conductivity of Clay Bricks - Bahar, Abely Aliya; Yulianto, Agus; Astuti, Budi (Rekayasa Sipil, 2024)
This research was conducted to find an alternative to the brick wall constituent material with the lowest thermal conductivity value by adding sawdust. The method of measuring the thermal conductivity value used is the steady-state hot plate method. From the test results obtained the more the addition of sawdust, the value of thermal conductivity obtained is also increasing. With the best conductivity value obtained by the author is in the addition of sawdust as much as 5 grams with a conductivity value of 0.006573945Q W/mK.